The geometry and timing of orogenic extension: An example from the western Italian Alps - Reddy, Steven; Wheeler, J.; Cliff, R. (Blackwells, 1999)
Contacts between rocks recording large differences in metamorphic grade are indicative of major tectonic displacements. Low-P upon high-P contacts are commonly interpreted as extensional (i.e. material points on either side of the contact moved apart relative to the palaeo-horizontal), but dating of deformation and metamorphism is essential in testing such models. In the Western Alps, the Piemonte Ophiolite consists of eclogites (T 550 600 C and P18 20 kbar) structurally beneath greenschist facies rocks (T 400 C and P9 kbar). Mapping shows that the latter form a kilometre-wide shear zone (the Gressoney Shear Zone, GSZ) dominated by top-SE movement related to crustal extension. Rb Sr data from micas within different GSZ fabrics, which dynamically recrystallized below their blocking temperature, are interpreted as deformation ages. Ages from different samples within the same fabric are reproducible and are consistent with the relative chronology derived from mapping. They show that the GSZ had an extensional deformation history over a period of c. 9 Myr between c. 45 36 Ma. This overlaps in time with the eclogite facies metamorphism. The GSZ operated over the entire period during which the footwall evolved from eclogite to greenschist facies and was therefore responsible for eclogite exhumation. The discrete contact zone between eclogite and greenschist facies rocks is the last active part of the GSZ and truncates greenschist facies folds in the footwall. These final movements were therefore not a major component of eclogite exhumation. Pressure estimates associated with old and young fabrics within the GSZ are comparable, indicating that during extensional deformation there was no significant unroofing of the hangingwall. Since there are no known extensional structures younger than 36 Ma at higher levels in this part of the Alps, exhumation since the final juxtaposition of the two units (at 36 Ma) seems to have been dominated by erosion.